SolaSolar Flare Effect to Sq Variation of Geomagnetic Field Observed at Biak Station from 1992 to 2003 - Visca Wellyanita; La Ode, Muhammad Musafar; Ahmad Zulfiana Utama; Mira Juangsih; Siska Filawati; Rizal Suryana; Setyanto Cahyo Pranoto; Yana Robiana; Refina Sri Fitri Wisnu (Indonesian Journal of Aerospace, 2024)
We analyzed the dependence of the geomagnetic Sq field variation at the Biak magnetic field observation station using data from a magnetometer from 1992 to 2003. The Biak station is a low magnetic latitude station, making the dominant variation of the magnetic field component that related to ionospheric currents representable by H-component. The Sq field was extracted from the magnetometer data using the 4th Harmonics Fourier decomposition method. This technique was applied to 1-hour average data of the H-component of the magnetic field. To investigate the dependence of the Sq field amplitude on solar flare events, we selected Sq field variations during flare events without magnetic storms. Additionally, before conducting the Fourier decomposition, we applied Dst index correction to the magnetic field variation data to eliminate the effects of magnetospheric currents. The study shows that Sq variation is highly correlated with X-class flares, which are the most energetic type of flares. Conversely, the lowest amplitude is linked to A-class flares with the lowest energy. These findings indicate that X-class flares generate Sq currents and induce the strongest magnetic fields compared to other classes of flares.